A survey of college and university libraries in Region I its implications to the Private Higher Education (PHE) Library Standards - Seng, Olga G. (Institute of Library Science, University of the Philippines Diliman, 1981)
The major purposes of this study are to investigate, assess, and analyze the problems which exist in and impede the development of private college and university libraries in Region I against the PHE Tentative Library Standards and to make recommendations for their improvement and development.